Long-term Swallowing Function, Pulmonary Complications, and Quality of Life after Supracricoid Laryngectomy. (August 2019) - Di Santo, Davide; Bondi, Stefano; Giordano, Leone; Galli, Andrea; Tulli, Michele; Ramella, Barbara; Bussi, Mario
Objectives: Long-term effects of supracricoid laryngectomies are nowadays under discussion. The purpose of this study was to detect the prevalence of chronic aspiration and incidence of pulmonary complications, to investigate possible influencing factors, and to analyze dysphagia-related quality of life in a cohort of patients who recovered swallowing function after undergoing supracricoid laryngectomies. Study Design: Retrospective observational study. Setting: San Raffaele Hospital, Vita-Salute University, Milan, Italy. Methods: A cohort of 39 patients who recovered swallowing function free of disease after a minimum 3-year follow-up period was retrospectively investigated between October and December 2017—clinically with the Pearson's Scale and M. D. Anderson Dysphagia Inventory and instrumentally with fiberoptic endoscopic evaluation of swallowing. Results: Chronic aspiration was demonstrated in a significant portion of patients (clinically in 33.3% and instrumentally in 35.9%). Aspiration was influenced by advanced age at surgery ( P = .020). Type of surgical procedure, resection of 1 arytenoid cartilage, postoperative rehabilitation with a speech-language therapist, radiotherapy, age at consultation, and length of follow-up did not influence the prevalence of aspiration. Pulmonary complications affected 5 patients; incidence of pulmonary complications was related to aspiration and was favored by poor laryngeal sensation/cough reflex. Aspiration significantly affected quality of life. Conclusions: Chronic aspiration is frequent and affects patients' quality of life. However, incidence of pulmonary complications is low; therefore, oral feeding should not be contraindicated for aspirating patients. Preservation of laryngeal sensation and cough reflex is mandatory to prevent pulmonary complications.